2018
DOI: 10.1109/tnsre.2017.2779135
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory TMS-EEG-Responses as a Measure of the Cortical Excitability Threshold

Abstract: Transcranial magnetic stimulation (TMS) is a non-invasive tool to perturb brain activity. In TMS studies, the stimulation intensity (SI) is commonly normalized to the resting motor threshold (rMT) that produces muscle responses in 50% of stimulations applied to the motor cortex (M1). Since rMT is influenced by spinal excitability and coil-to-cortex distance, responses recorded from the cortex, instead of a peripheral muscle, could provide a more accurate marker for cortical excitability. Combining TMS with ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…After adjusting for the individual RMT of each pulse type, the following findings were found: (i) GMFP was higher with monophasic pulses (P < 0.001); (ii) local mean field power was higher with longer pulse width (P = 0.015); (iii) early TEP polarity was modulated depending on the current direction (P = 0.01). Saari et al, 2018 70 This study provides support for earlier intracranial electrical stimulation findings as it demonstrates cerebellar involvement in the alteration of core frequencies linked to cognitive and emotive aspects of human behavior. 78 Paired-pulse TMS: Intracortical facilitation -M1 and DLPFC ICF is a pp-TMS paradigm composed of a subthreshold conditioned stimulus and a suprathreshold test stimulus that produces MEP facilitation at ISI of 7 to 30 ms, 33 thought to be associated with both GABA(A) 34 and NMDA 35 receptors.…”
Section: Single-pulse Tms: M1supporting
confidence: 80%
“…After adjusting for the individual RMT of each pulse type, the following findings were found: (i) GMFP was higher with monophasic pulses (P < 0.001); (ii) local mean field power was higher with longer pulse width (P = 0.015); (iii) early TEP polarity was modulated depending on the current direction (P = 0.01). Saari et al, 2018 70 This study provides support for earlier intracranial electrical stimulation findings as it demonstrates cerebellar involvement in the alteration of core frequencies linked to cognitive and emotive aspects of human behavior. 78 Paired-pulse TMS: Intracortical facilitation -M1 and DLPFC ICF is a pp-TMS paradigm composed of a subthreshold conditioned stimulus and a suprathreshold test stimulus that produces MEP facilitation at ISI of 7 to 30 ms, 33 thought to be associated with both GABA(A) 34 and NMDA 35 receptors.…”
Section: Single-pulse Tms: M1supporting
confidence: 80%
“…Several studies show no difference in resting motor threshold between people with migraine and controls [11][12][13][14][15]. Combining TMS with EEG offers new options to assess cortical excitability, bypassing sensory and motor areas [16,17]. Previous TMS-EEG studies in epilepsy investigating TMS-evoked potential and the epileptiform EEG discharges triggered by TMS have identified aberrant excitability and connectivity [18][19][20][21][22][23][24] The only TMS-EEG study in JME to date found increased amplitude potentials in JME compared to controls, and increased amplitude of late peaks when participants with JME were sleep deprived, demonstrating cortical hyperexcitability (Del Felice 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One novel way of assessing cortical excitability using TMS-EEG is by determining the uniformity of phase angles across trials in EEG responses, [17]. On a single electrode, the phase of TMS evoked responses align between trials shortly after the TMS pulse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by stimulating the brain with external magnetic pulses-transcranial magnetic stimulation (TMS)-and recording EEG spectra and/or fMRI images, one can get information about correlations in time and space. [20,[121][122][123][124][125][126] Tononi's information integration theory (IIT) [22,23] treats consciousness as a global irreducible state of a complex system characterised by a single parameter describing the information content. The parameter is effectively obtained by averaging the EEG output from repeated TMS pulses and zip-compressing the output data.…”
Section: Current Paradigms: Gnw and Iitmentioning
confidence: 99%